On the Stability of Microfoams - YAN, YONG-LI; CHEN, JIE-RONG; WANG, YONG-WEI (Asian Journal of Chemistry, 2010)
Microfoams are finding increasing applications in separation processes. The stability of microfoams is a key parameter in these processes. The aim of this work is to derive the drainage mechanisms of microfoams by measuring drainage rates of the dispersions. Results show that the drainage of liquid from microfoams is divided into two stages of independent mechanisms. The primary drainage follows zero-order chemical reaction kinetics, while the second stage involving the films rupture and the bubbles coalesce is comparatively much slower. The effects of surfactant concentration used to produce microfoams in the presence of the electrolyte, such as sodium chloride, on the stability of the suspensions were also studied. The ordered molecular microstructures emerge when the concentrations of surfactant are above the value of the critical micellar concentration in the system, which plays an important role in stabilizing foam lamellae. The effect of the addition of sodium chloride on the stability of microfoams varies with the concentration of salt added in the continuous phase.